FACTORS AFFECTING THE REJECTION OF EVALUATION RADIOGRAPH BLASS NIER OVERZICHT-INTRAVENOUS PYELOGRAFI - Agi Febrian Trihadijaya; Retno Novia Masithoh; Maizza Nadia Putri; Talitha Arabella Hanum (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2016)
This research due to know the influencing factors of BNO-IVP radiograph rejection and to know the solution of rejection. The researcher using 3 method of data collecting, i.e. observational method which result the check-list of BNO-IVP rejected influencing factors, interview method which use to validate the data, and documentating method which result the data in photograph of BNO-IVP radiograph rejected. Then the data will be analysed with reject film analysis. Based on the method, the reject rate result on September up to 13,04%, on October up to 13,63%, then on November up to 29,26%. The influencing factors of BNO-IVP rejection i.e. un-cover anatomical region, poor of radiograph contrast, patient movement, fecal materials, and un-effectiveness of patient preparation. This research has been did on Department of Radiodiagnostic of RSUD Dr. Soetomo Surabaya using 12 BNO-IVP radiograph rejected of 41 total exams on November and then rated by 1 responden. Un-effectiveness of patient preparation is the result of this research. This factor is the main influencing factor of rejection up to 100%. Based on the researher analysis about the solution, i.e. increasing the communication to the patient about the BNO-IVP exam preparation and do revision to the patinet preparation form guide more simply, so the patient can understand easly.